Error Analysis of Students’ Pronunciation in Pronouncing English Vowels And Consonants - Niagara Ramses Pandapotan Hutapea; Nurhalimah Lubis; Sondang Manik; Lastri Wahyuni Manurung (Jurnal Pendidikan dan Konseling (JPDK), 2023)
This final project is a study about Error Analysis Of Students’ Pronunciation in Pronouncing English Vowels And Consonants of SMK Swasta Harapan Baru Medan in the Academic Year 2023/2024. (A case Study of the Eleventh Grade of SMK Swasta Harapan Baru Medan in the Academic Year 2023/2024). Most of the students may have problems to pronounce English vowels and consonants, although they get an English subject in their school and they can not master the English pronunciation well. Therefore, the students often make problem. This study was conducted under the consideration that pronouncing English vowels plays an important role. The problems of this study are what kinds of problem the students make in pronouncing English vowels and why these problem happen/occur. The purposes of the study are to find out kinds of problem made by students in pronouncing English vowels and consonants and to find out the factors why these problem happen/occur. The population of this study was the Eleventh grade of SMK Swasta Harapan Baru Medan in the Academic year of 2023/2024. Before the test doing the test, the writer observed the condition of the classroom during the language learning process. The writer wants to know the way how teacher explains the material and what the students are doing during the lesson. The instrument used by the writer in this final tape recorder which were used to record the students’ pronunciation. In analyzing the data, error analysis was used in which there were three steps: transcribing the students’ pronunciation into the phonetic transcriptions, problem in pronouncing English short vowels, problem in pronouncing English long vowels. Finally, the result of the analysis shows that students are considered “Enough” in pronouncing English vowels and consonants.